The Effectiveness Of Teacher Communication In Online And Offline Learning After The Covid 19 Pandemic - Maulana Fitroh Rahmawan (Journal of Social Science and Humanities, 2023)
In order for the material delivered by the teacher to be well received and understood by students, effective communication is needed, with effective communication it will facilitate the learning process and interaction between teachers and students. The arrival of the Covid 19 pandemic has affected various fields, one of which is education, almost all schools in Indonesia implement distance or online learning, in this online learning there are many obstacles in practice, including limited teacher communication, inadequate technology, as well as many obstacles. Therefore, many people choose and are happy if learning can be done face-to-face at school or offline. Many people find offline learning much more effective than online learning. This study aims to determine the effectiveness of teacher communication in online and offline learning. The method in this study uses qualitative research methods with descriptive studies. This study aims to determine how effective teacher communication is in online and offline learning. The results of this study indicate that the communication carried out by the teacher in offline learning is much more effective when compared to online learning, because in offline learning there are many obstacles and obstacles that affect the effectiveness of the communication carried out by the teacher.